Novel Method to Image and Quantify Cogwheel Structures in Foraminiferal Shells - van Dijk, Inge; Raitzsch, Markus; Brummer, Geert-Jan A.; Bijma, Jelle (Frontiers in Ecology and Evolution, 2020)
Most studies designed to better understand biomineralization by foraminifera focus mainly on their shell chemistry in order to retrace processes responsible for element uptake and shell formation. Still, shell formation is a combination of not only chemical and biological processes, but is also limited by structural features. Since the processes involved in the formation of the foraminiferal shell remains elusive, new focus has been put on potential structural constraints during shell formation. Revealing structural details of shells of foraminifera might increase our mechanistic understanding of foraminiferal calcification, and even explain species-specific differences in element incorporation. Recently, shell structures have been studied in increasingly higher resolution and detail. This paper aims to provide new insights on the structural features on foraminiferal shells, so-called cogwheels, which can be observed in the shell wall and at its surface. Here, we present a novel method to image and quantify these cogwheel structures, using field specimens from different environments and ecological groups, including benthic and planktonic species. Application of this method allows for comparing shell structures at specimen and species level, to unravel potential drivers of shell formation.